The contribution of school culture and job motivation to the performance of chemistry teachers - Fatmawati, Fatmawati (Jurnal Inovasi Pendidikan IPA, 2017)
The study aimed at identifying the contribution of school culture and job motivation as an aggregate to the performance of senior high school/madrasah aliyahs/vocational high school Chemistry teachers in Nunukan and Sebatik District, the Province of North Borneo. The study was an ex-post facto research. The sample in this study was selected using census technique or saturated sampling technique and there were 28 senior high school/madrasah aliyahs/vocational high school Chemistry teachers in Sebatik and Nunukan District. The data were gathered using inventory instrument, interview, and documentation which validity and reliability had been tested. The data were analyzed using multiple linear regressions. The results of the study show that school culture and job motivation altogether has positive and significant contribution to the performance of senior high school/madrasah aliyahs/vocational high school Chemistry teachers in Sebatik and Nunukan District and the contribution size is 0.639 or 63.90%. This statement implies that most of senior high school/madrasah aliyahs/vocational high school Chemistry teachers in Nunukan and Sebatik District have been influenced by good school culture and job motivation simultaneously